Reconciling the Effects of Screening on Prostate Cancer Mortality in the ERSPC and PLCO Trials - Tsodikov, Alex; Gulati, Roman; Heijnsdijk, Eveline A M; Pinsky, Paul F; Moss, Sue M; Qiu, Sheng; de Carvalho, Tiago M; Hugosson, Jonas; Berg, Christine D; Auvinen, Anssi; Andriole, Gerald L; Roobol, Monique J; et al. (Annals of internal medicine, 2017)
The ERSPC (European Randomized Study of Screening for Prostate Cancer) found that screening reduced prostate cancer mortality, but the PLCO (Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial) found no reduction. To evaluate whether effects of screening on prostate cancer mortality relative to no screening differed between the ERSPC and PLCO. Cox regression of prostate cancer death in each trial group, adjusted for age and trial. Extended analyses accounted for increased incidence due to screening and diagnostic work-up in each group via mean lead times (MLTs), which were estimated empirically and using analytic or microsimulation models. Randomized controlled trials in Europe and the United States. Men aged 55 to 69 (ERSPC) or 55 to 74 (PLCO) years at randomization. Prostate cancer screening. Prostate cancer incidence and survival from randomization; prostate cancer incidence in the United States before screening began. Estimated MLTs were similar in the ERSPC and PLCO intervention groups but were longer in the PLCO control group than the ERSPC control group. Extended analyses found no evidence that effects of screening differed between trials (P = 0.37 to 0.47 [range across MLT estimation approaches]) but strong evidence that benefit increased with MLT (P = 0.0027 to 0.0032). Screening was estimated to confer a 7% to 9% reduction in the risk for prostate cancer death per year of MLT. This translated into estimates of 25% to 31% and 27% to 32% lower risk for prostate cancer death with screening as performed in the ERSPC and PLCO intervention groups, respectively, compared with no screening. The MLT is a simple metric of screening and diagnostic work-up. After differences in implementation and settings are accounted for, the ERSPC and PLCO provide compatible evidence that screening reduces prostate cancer mortality. National Cancer Institute.